A New Method For Passive Ankle Foot Orthosis Design – Integration Of Musculoskeletal And Finite Element Simulation - Scherb, David; Steck, Patrick; Völkl, Harald; Wartzack, Sandro; Miehling, Jörg (Proceedings of the Design Society, 2023)
Motor disorders are diseases affecting the muscle function of the human body. A frequently occurring motor disorder affects the lower leg muscles resulting in a pathological gait called foot drop. Patients have a higher risk of stumbling and falling. The most common treatment is the use of a passive ankle-foot-orthosis (AFO). However, the compensation of foot drop is only limited due to the non possible support of all rotational directions of the ankle joint. Therefore, a newly developed concept for a passive AFO is currently in work. To ensure a best possible treatment of the patient, the provided support by the AFO and required support by the patient have to be in accordance. Thus, in this contribution a method is presented that integrates model order reduced finite element analysis for computing the provided support of the AFO and musculoskeletal human models for representing the patients' gait behaviour. With the method, the design of the force generating structures of the AFO can be realized regarding the patients' requirements. The presented method is further evaluated with a specific use case. The main focus lies here in the principal functionality of the method and the provision of valid results.<br
Keywords: User centred design; Design methods; Product modelling / models; Orthosis; Musculoskeletal human model